Time on Target : The World War II Memoir of William R. Buster - Buster, William R. (Book collections on Project MUSE., 1999)
William R. Buster, born in Harrodsburg, Kentucky, knew a soldier's combat experience and left a first hand account of it. He graduated from West Point in 1939, just in time to serve through one of the most crucial periods in national and world history. His story includes accounts of the incredible expansion, arming, and training of the US Army, as well as his experience in the great conflict itself, from North Africa and Sicily to the hedgerow country of Normandy, the Battle of the Bulge, and on to Berlin. For his service, he received the Silver Star with Oak Leaf Cluster, the Bronze Star, the ...